How Does Information Spread on Social Media Lead to Effective Change? - Varghese, Thomas K., Jr. (Clinics in Colon and Rectal Surgery, 2017)
Social media encompasses computer-mediated technologies that facilitate the creation and sharing of information, ideas, and other forms of expression via virtual communities and networks. The key, of course, is the ability and willingness for information to be shared. But why does some information spread on social media and not others? What factors translate social media awareness to action? In this article, we explore these themes using case studies, as well as tips on how you can utilize social media to effectively champion a cause.
Keywords: social media; awareness; virtual communities